The Influence of Traditional Bakiak Game on Gross Motor Skills in Early Childhood - Yuningsih, Restu; Soniati, Soniati; Sari, Meliana; Nurhasanah, Nurhasanah (Journal of Islamic Education Students (JIES), 2023)
This study aims to explore the influence of traditional bakiak games on the gross motor skills of early childhood. The research adopts a quantitative approach with an experimental design, specifically utilizing a pre-experimental One Group Pretest-posttest design. The participants include all children at Mutiara Bunda Early Childhood Education (PAUD), amounting to 18 children, who were selected using a total sampling technique. Data were collected through observation sheets. Prerequisite tests, such as normality and homogeneity tests, were conducted, followed by hypothesis testing using the t-test. The findings indicate that the t-table value at a significance level of 5% supports the research hypothesis, leading to the rejection of the null hypothesis and the acceptance of the alternative hypothesis. The findings of this research underline the importance of incorporating traditional games like bakiak into early childhood education to enhance gross motor skills.